AKIBAT HUKUM PEMBATALAN SEPIHAK MASKAPAI LION AIR YANG MERUGIKAN PIHAK PENUMPANG BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 2009 TENTANG PENERBANGAN (STUDI KASUS ATAS PUTUSAN NOMOR 471 PK/PDT/2017). - Andreas Even Limarus; Amad Sudiro (Jurnal Hukum Adigama, 2021)
Indonesia has thousands of islands, therefore transportation is needed that can cross the island, one of which is an airplane, this transportation is very much needed to travel anywhere but airlines in Indonesia sometimes make negligence that harms passengers. legal consequences of unilateral cancellation by Lion air airline against passengers. 471 PK/PDT/2017 In the case of legal consequences of unilateral cancellation of Lion Air Airlines which are detrimental to the Passengers based on Law Number 1 of 2009 concerning Aviation. Researchers use the normative method that is based on the law. To regulate the responsibility of the researcher, the focus is on Law Number 1 of 2009 concerning Aviation and the Civil Code. The data and theory used by the researcher shows that there are errors that arise from the airline, where passengers come to the airport and when they want to check-in and when they want to check-in other passengers cannot fly because of the full capacity of the aircraft. We recommend that if there are no urgent circumstances from physical limitations, there is no need to provide a check-in queue which makes check-in impossible